The determinants of vulnerability to the global financial crisis 2008 to 2009: Credit growth and other sources of risk - Martin Feldkircher (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
In this paper, we identify initial macroeconomic and financial market conditions that help explain the distinct response of the real economy of a particular country to the recent global financial crisis. Using four measures of crisis severity, we examine a data set with over 90 potential explanatory factors employing techniques that are robust to model uncertainty. Four findings are of particular note. First, we find empirical evidence for the pivotal role of pre-crisis credit growth in shaping the real economy's response to the crisis. Specifically, a 1% increase in pre-crisis lending translates into a 0.2% increase in the cumulative loss in real output. Moreover, the combination of pronounced growth in lending ahead of the crisis and the country's exposure to external funding from advanced economies is shown to intensify the real downturn. Economies with booming real activity before the crisis are found to be less resilient to the global shock. Buoyant growth in real GDP in parallel with strong growth of credit particularly exacerbated the effects of the recent crisis on the real economy. Finally, we provide empirical evidence on the importance of holding international reserves in explaining the response of the real economy to the crisis. The effect of international reserves accumulation as a shelter to the global shock rises in credit provided by the domestic banking sector. The results are shown to be robust to several estimation techniques, including those allowing for cross-country spillovers.
URN:NBN:fi:bof-201408071971
Keywords: C11; C15; E01; O47; 330; Financial crisis; credit boom; international shock transmission; Bayesian model averaging; cross-country analysis; non-linear effects